Job Satisfaction as Mediator in the Effect of Perceived Organizational Support on Employee Engagement: Evidence from SMEs in Indonesia - Siregar, Zulkifli Musannip Efendi; Lubis, Tukimin; Syamsuri, Abd. Rasyid; Siregar, Dede Iskandar; Supriadi, Yudi Nur (Universitas Brawijaya, Indonesia, 2024)
Small and medium enterprises (SMEs) have become a cornerstone of Indonesia's economic growth, yet employee engagement remains a significant challenge that often hampers their performance. Enhancing employee engagement is crucial for driving business success and achieving optimal results. Employee work engagement is very important in enhancing a company's success. This research constructs the relationship model that shows how employee engagement, job satisfaction, and perceived organizational support relate to employees. The study was carried out at SMEs and employees as respondents. The research used a quantitative approach. Data was collected through online questionnaires, and the data was collected from 141 respondents. Sample selection was carried out using the snowball sampling method. The data that has been successfully collected were processed by using SEM Smart PLS. The results of this study show an influence between perceived organizational support and job satisfaction. Employee work engagement is positively influenced by job satisfaction, and perceived organizational support positively impacts employee work engagement. In addition, studies have demonstrated the critical role that job satisfaction plays as a mediating factor in the relationship between employees' perceived organizational support and worker engagement. This research has implications for improving organizational support, such as appreciation, respecting employee ideas and opinions, and paying attention to employee job satisfaction to increase employee engagement.